Writing the worlds of genomic medicine: experiences of using participatory-writing to understand life with rare conditions. Issue 2 (13th April 2022) - Gorman, Richard; Farsides, Bobbie
Abstract : The diagnostic and treatment possibilities made possible by the development and subsequent mainstreaming of clinical genomics services have the potential to profoundly change the experiences of families affected by rare genetic conditions. Understanding the potentials of genomic medicine requires that we consider the perspectives of those who engage with such services; there are substantial social implications involved. There are increasing calls to think more creatively, and draw on more participatory approaches, in evoking rich accounts of lived experience. In this article, we discuss our rationale for, and experiences of, using 'participatory-writing' to understand the diverse, variable and multilayered everyday lives of families and how these correspond with the emerging, rapidly changing and complex field of genomic medicine. Participatory-writing has many benefits as a method for social inquiry. Writing can be expressive and self-revelatory, providing insight into personal and sensitive topics. Writing together produces new conversations and relationships. Pieces written by participants have the potential to affect readers, evoking and enlivening research and prompting professional change. Working with a writing tutor, we organised a participatory-writing programme for families touched by genetic conditions. This involved a series of workshops with an emphasis on building confidence in expressing lived experience through experimenting with different writing techniques. Afterwards we arranged reflective interviews with participants. We drew on dialogical narrative analysis to engage with participants' written pieces, and highlight what everyday life is like for the people who live with, and care for, those with genetic conditions. The stories produced through our writing-groups unfold the implications of new genomic technologies, illuminating how genomics acts to (and likewise, fails to) reconfigure aspects of people's lives outside of the clinic, while simultaneously existing as a sociotechnical frame that can eclipse the wider contexts, challenges and liveliness of life with rare genetic conditions.